A Study of Tenth Students’ Speaking Ability in Asking and Giving Opinions - Rizka Elia; Widya Juli Astira; Lailatul Husna (Kilau Publishing, 2025)
The aims of the research was to analyze the students’ speaking skills and identify the difficulties that encountered by the students in asking and giving opinions at the tenth grade of SMKN 5 Padang, such as limited vocabulary, mispronunciation, and difficulty in distinguishing expressions used for asking and giving opinions. This research used a descriptive method. The researchers used a cluster random sampling technique on two classes, namely X TKRO 1 and X TKRO 2 at SMKN 5 Padang. The selected class was X TKRO 1, which consisting of 30 students. The data were collected through a speaking test where students performed dialogues in asking and giving opinions in front of the class. The data were analyzed based on the criteria of speaking skill components.The results showed that the speaking skill of students in class X TKRO 1 in asking and giving opinions was at moderate, with the mean score 69.3, reflecting their performance in the analyzed aspects such as fluency, accuracy, pronunciation, grammar, and vocabulary.